2020
DOI: 10.5152/ejbh.2020.5198
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Link between Lynch Syndrome and Breast Cancer

Abstract: Lynch syndrome is an inherited cancer-susceptibility disorder caused by pathogenic germline variants in DNA mismatch repair (MMR) genes, including MLH1, MSH2, MSH6, and PMS2. Historically known as hereditary nonpolyposis colorectal cancer, this syndrome is associated with increased risk for a multitude of cancers, including colorectal, endometrial, ovarian, small bowel, urothelium, biliary tract, and stomach (1-3). Lynch syndrome affects 1 in 279 individuals, and is more common than Hereditary Breast and Ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Consensus in the literature is that there is no statistically significant association between germline mutations in these MMR genes and breast cancer risk [ 53 ]. However, some studies do identify an increased risk of breast cancer incidence, and younger age at diagnosis in women with germline variants in PMS2 and MSH6, but no association with germline mutations in MLH1 or MSH2 [ 54 , 55 ]. A recent study conducted in a cohort of 711 patients with hereditary breast cancer, reported that 69 (9.7 %) patients had at least one germline mutation in the MMR genes.…”
Section: Mismatch Repair Alterations In Hr+ Breast Cancermentioning
confidence: 99%
“…Consensus in the literature is that there is no statistically significant association between germline mutations in these MMR genes and breast cancer risk [ 53 ]. However, some studies do identify an increased risk of breast cancer incidence, and younger age at diagnosis in women with germline variants in PMS2 and MSH6, but no association with germline mutations in MLH1 or MSH2 [ 54 , 55 ]. A recent study conducted in a cohort of 711 patients with hereditary breast cancer, reported that 69 (9.7 %) patients had at least one germline mutation in the MMR genes.…”
Section: Mismatch Repair Alterations In Hr+ Breast Cancermentioning
confidence: 99%
“…The distribution of MMR gene pathogenic mutation in LS-CRC in China was as follows: MLH1 39.1 %, MSH2 33.9 %, MSH6 12.2 %, PMS2 9.6 % [ 4 ]. According to the studies from non-Asian population, MSH2 and MSH6 are the main susceptibility genes for ovarian cancer [ 25 ], MSH2 for urinary tract cancer [ 21 ], and PMS2 for breast cancer [ 26 ]. These LS-RC have not been fully studied in Asian population.…”
Section: Ls-related Cancers and Mmr Mutations In Chinamentioning
confidence: 99%
“…Some reports mentioned that LS is associated with a higher risk of breast cancer (up to two fold), in particular with MSH6 and PMS2 mutations as well as cases of MSI. The other observation is that age at diagnosis is younger in carrier cases with mismatch repair defects exhibited in the breast tumors [16][17][18]. Ford et al, in 2012, suggested a wider prospective study to assess if breast cancer is a component of LS as well as to evaluate the prognostic and predictive value of MSI in breast cancer management [16].…”
Section: Discussionmentioning
confidence: 99%